A deep learning based multimodal fusion model for skin lesion diagnosis using smartphone collected clinical images and metadata - Ou, Chubin; Zhou, Sitong; Yang, Ronghua; Jiang, Weili; He, Haoyang; Gan, Wenjun; Chen, Wentao; Qin, Xinchi; Luo, Wei; Pi, Xiaobing; Li, Jiehua (Frontiers in Surgery, 2022)
Introduction Skin cancer is one of the most common types of cancer. An accessible tool to the public can help screening for malign lesion. We aimed to develop a deep learning model to classify skin lesion using clinical images and meta information collected from smartphones. Methods A deep neural network was developed with two encoders for extracting information from image data and metadata. A multimodal fusion module with intra-modality self-attention and inter-modality cross-attention was proposed to effectively combine image features and meta features. The model was trained on tested on a public dataset and compared with other state-of-the-art methods using five-fold cross-validation. Results Including metadata is shown to significantly improve a model’s performance. Our model outperformed other metadata fusion methods in terms of accuracy, balanced accuracy and area under the receiver-operating characteristic curve, with an averaged value of ??, ?? and ??. Conclusion A deep learning model using smartphone collected images and metadata for skin lesion diagnosis was successfully developed. The proposed model showed promising performance and could be a potential tool for skin cancer screening.